'HYPERTENSION PREVALENCE, AWARENESS, TREATMENT AND CONTROL STATUS AMONG THE HEALTHCARE PROVIDERS OF BANGLADESH WORKING AT PRIMARY HEALTH CARE LEVEL. (April 2021) - Faruque, Mithila; Barua, Lingkan; Banik, Palash Chandra
Abstract : Objective: This study aimed to determine the prevalence of hypertension and awareness, treatment and control status of hypertension among the primary healthcare providers of Bangladesh. Design and method: This was a cross-sectional study conducted among 1912 senior stuff nurses (SSN) and para-health professionals who came to attend a 3-day training in Bangladesh University of Health Sciences (BUHS) during November 2017 to April 2018. The study population was selected by the Government from all districts of Bangladesh. Data were collected using STEPS questionnaire of World Health Organization. Two blood pressure measurements were obtained by trained observers by use of a mercury sphygmomanometer. Information on history of hypertension and use of antihypertensive medications was obtained by use of a standard questionnaire. Hypertension was defined as systolic and/or diastolic blood pressure equal or more than 140/90 mmHg or a self-reported diagnosis of hypertension and/or use of antihypertensive medications according to JNC 7 guidelines. Results: The mean age of the population was 37.63 ± 9.5 years and their average duration of employment was 13.8 ± 9.5. Among the total, 29.7% (95% CI, 2 7.7–31.7) of the healthcare providers had hypertension, 67.4% were aware of their hypertension and 88.7% of them were taking antihypertensive medication. But only 40.8% attained blood pressure control. The overall prevalence of hypertension was slightly higher among men than among women. The prevalence of hypertension was found increased with age. The age specific prevalence of hypertension was 16.3% (95% CI, 14.6–18.0), 22.9% (95% CI, 21.0–24.8), 42.1% (95% CI, 39.9–44.3) and 49.8% (95% CI, 47.6–52.0) among 20–29, 30–39. 40 49 and equal or more than 50 years age groups respectively. Added salt intake, diabetes mellitus, central obesity and generalized obesity were significantly associated with hypertension (p < 0.05). Age and diabetes mellitus was two significant predictors of hypertension. Figure. No caption available. Conclusions: Hypertension is highly prevalent among the healthcare providers of Bangladesh working at primary healthcare level. More than two-third are aware that they have hypertension but controlled rate by anti-hypertensive is low. These results underscore the urgent need to develop national strategies for detection and treatment of hypertension among these service providers.